The socioeconomic structure of fishermen of Iznik lake - (:unkn) unknown (AMER FISHERIES SOC, 2008)
Although fishing for freshwater foods has long been common in Turkey, this and related industries have not achieved targeted production levels in recent years. In this study, we explore the socioeconomic characteristics of Iznik Lake fishermen in order to identify conditions affecting their production. Overfishing of the seas and lakes of Turkey has contributed to a significant decline in the production of freshwater resources. Production was 676,004 metric tons in 1988. It declined to 364,661 metric tons in 1991. Whlie this value rose to 582,376 metric tons in 2000, this increase is nonetheless considered insufficient relative to the rising population. Iznik Lake is located very near Istanbul, the largest city and metropolitan area in Turkey. With an area of 298 km(2), Iznik is the largest lake of the Marmara Region. These features contribute to the pertinence of our investigation. Furthermore, the needs and conditions of fishermen who live in the region are also important issues. Our research subjects are fishermen who live and work in and around Iznik Lake. Individual informants were asked questions about their family and their work in order to assess various characteristics of the workforce community, including general demographic information, average age, number of workers, education level, production capacity, production technology, export-import situation, and transportation. The socioeconomic structure of the Iznik Lake fishing community is described using the data we collected. This study will provide important baseline data and will serve as a methodological example for further research in this field.